Pelatihan Pengolahan Ikan Bandeng Isi Tanpa Tulang Bersama Kelompok Wanita Tani (KWT) Meugah Raya - Azhar, Rossy; Irfannur, Irfannur; Akmal, Yusrizal; Husna, Asmaul; Nuraida, Nuraida; Fridayati, Diah; Hakim, Syahirman (Aceh Journal of Community Engagement (AJCE), 2023)
Field Lectures and Community Service activities with the theme "Training on Processing Boneless Stuffed Milkfish with the Meugah Raya Women Farmers Group (KWT)". Activities are carried out in 4 stages, namely preparation of activity proposals, preparation of tools and materials for activities, implementation of activities and preparation of activity reports. The results achieved from this service are: Conduct training to the community about milkfish processing; Increase public awareness of the importance of fish processing if fish production is abundant; Create the latest ways of processing fish in farm women's groups; Increase economic value for farm women's groups in processing fish; Motivate students and the community to be more innovative and productive in processing fish; Sustainability of activities carried out with continuity by Lecturers and Students of the Faculty of Agriculture, Almuslim University